COVID-19 and hand hygiene: the vital importance of hand drying. (24th September 2020) - Gammon, John; Hunt, Julian
Abstract : The significance of hand hygiene for preventing the transmission of microorganisms and reducing the spread of infection has been brought into sharp focus following the global coronavirus (COVID-19) pandemic. In the months since the initial outbreak, international public health campaigns and practitioner education has concentrated on hand washing and hand sanitising, with very little reference to hand drying, if any at all. However, hand drying is integral to effective hand hygiene, and is important in controlling the spread of microorganisms and maintaining healthy skin integrity. This research commentary will focus on two issues of importance with regards to hand drying: microbial transmission and skin irritation, with implications for healthcare practitioners and practice considered. It is argued that a more holistic approach to hand hygiene must be the ambition if health professional and public behaviour is to become embedded and sustained.